How microsaccades relate to lateralized ERP components of spatial attention: A co-registration study. (May 2017) - Meyberg, Susann; Sommer, Werner; Dimigen, Olaf
Abstract: Covert shifts of attention that follow the presentation of a cue are associated with lateralized components in the event-related potential (ERP): the "early directing attention negativity" (EDAN) and the "anterior directing attention negativity" (ADAN). Traditionally, these shifts are thought to take place while gaze is fixated and, thus, in the absence of saccades. However, microsaccades of small amplitude (<1°) occur frequently and involuntarily also during fixation and are closely correlated with spatial attention. To investigate potential links between microsaccades and lateralized ERP components, we simultaneously recorded eye movements and ERPs in a spatial cueing task. As a first major result, we show that both the posterior EDAN and the orientation of microsaccades align more strongly with the location of the task-relevant part of the cue stimulus than with the direction of the attention shift indicated by that cue. A coupling between microsaccades and EDAN was also present on the single-trial level: The EDAN was largest when microsaccades were oriented toward the relevant cue, but absent when microsaccades were oriented away from it, suggesting that EDAN and microsaccades are generated by the same neural network, which selects relevant stimuli and orients behavior toward them. As a second major result, we show that small corneoretinal artifacts from microsaccades, which fall below conventional EOG rejection thresholds, contaminate the measurement of the ADAN. After correcting the EEG for microsaccade-related artifacts with an optimized variant of independent component analysis, ADAN was abolished at frontal sites, but a genuine ADAN was still present at central sites. Thus, the combined measurement of microsaccades and lateralized ERPs sheds new light onto cue-elicited shifts of covert attention. Highlights: We co-recorded microsaccades (MSs) and ERPs in a covert attentional cueing task. Ocular artifacts from MSs were corrected with a new ICA procedure. Artifacts from MSs distort but do not fully explain frontal cue-related ERPs (ADAN). MS direction correlates with posterior cue-ERPs (EDAN) on the single trial level. This link is likely based on a shared process of selecting relevant cue features.